Dogs in Batak Simalungun and English Proverbs - Malau, Putri Pridani; Suhandano (Talenta Publisher, 2024)
This article discusses dog metaphors in Batak Simalungun (BS) and English (ENG) proverbs. This study aims to identify the meaning features and interpret the perception of the people who speak both languages towards dogs reflected in their proverbs. The research used a qualitative descriptive method. Data were collected from two sources, namely written sources and oral sources. The data were analyzed with an anthropological linguistic approach, namely looking at the meaning features of dogs in both languages and interpreting them in the cultural context of the speakers. The results show that the dominating dog meaning feature in the proverbs of both languages is the nature of dogs. The meaning feature found in BS proverbs is only one meaning feature, which is about dog behavior. The dog meaning features in ENG proverbs have six meaning features, including dog traits (i.e., behavior, size, quality, and condition), body parts, position, age, dog day, and love for dogs. The things that influence the differences in the meaning features of dogs in the proverbs of the two languages consist of the speakers' environmental factors and social factors. The similarity of perception towards dogs in the culture of BS speakers and ENG speakers is the position of dogs, which are referred to as human friends and pets.